Pelabuhan Teluk Betung dalam Jaringan Maritim Nusantara, 1891-1941 - Maylatul Luvi; Abd Rahman Hamid; Aan Budianto (Universitas Hamzanwadi, 2025)
In the early 20th century, Lampung became one of the key regions within the maritime network of the Nusantara. In this context, the Port of Teluk Betung functioned as a link between inland areas producing various commodities and major ports. Through the operations of KPM vessels, this port became integrated into the colonial maritime transportation system, which accelerated the distribution of agricultural products, particularly pepper, coffee, and rubber. This study aims to explain the role of Teluk Betung as a collecting centers, analyze the contribution of KPM in expanding trade networks, and understand the development of major commodities that supported Lampung’s economy. The research employs the historical method, consisting of four stages: heuristics, source criticism, interpretation, and historiography. The findings indicate that Teluk Betung functioned not only as a local port for collecting agricultural products and a hub of maritime activities but also as a regional and international port. Its existence facilitated the flow of commodities and population mobility while also marking the economic and social transformation of Lampung as an integral part of the global economic system of the Nusantara.